Diseño e implementación de un sistema automatizado de aprovechamiento y control de agua en la empresa hormigones ecuador. - Espinosa Berrazueta, Lesly Eliana (2019)
The automation of a system allows to improve working conditions in addition, to reduce production costs so that they are more efficient, so automation was developed in the control of the storage tank, and in the dosage of the liquid in the company Hormigones Ecuador located in Quito city through the use of an ultrasonic sensor that measures two levels one maximum and minimum, a flowmeter that is responsible for measuring the amounts of water at the discharge point, which considers values according to resistance having a relation of liters per cubic meter. The system of censorship allows to enable the operation of the pump through water levels one maximum and one minimum sending a pulse of current that activates a relay and this puts the pump into operation it is responsible for transporting the liquid whenever the order is executed considering an on-off system, the same that comes from a reuse system of the washing of mixers, this water goes through a cleaning process so that it is useful for a new production. Taking water properties from water density 0.97g / ml, viscosity of 0.001kg / ms and a pH of 9, these values being stable for the final product. To transport of fluid, an optimal diameter of 2 inches was established, the pipe of PVC material and accessories of PVC and galvanized iron. Due to the shape of the tank, Bernoulli's characteristic equation was used, which allowed to identify the errors given by the dispatch flow, having as variable the heights of the tank an atmospheric pressure at the different points and a resistance given by the flow meter, Matlab program was used develop the characteristic curve of the system, ending in the HMI design using the Review program that executes the automation processes, to improve production processes and reducing fluid losses, labor.